2016
DOI: 10.1007/s00198-016-3826-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-dose cholecalciferol (vitamin D3) on bone and body composition in children and young adults with HIV infection: a randomized, double-blind, placebo-controlled trial

Abstract: Despite increasing 25(OH)D concentrations, 12 months of high-dose vitamin D supplementation did not impact bone or body composition in children and young adults with HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Intervention studies with vitamin D supplementation have confirmed this lack of correlation. Although daily supplementation with high-dose cholecalciferol (vitamin D3) in children and young adults with HIV infection for 12 months resulted in increased 25(OH)D concentrations, no impact was found on bone density, structure, and strength [42]. Similarly, PTH and bone turnover markers were not associated with 25(OH)D at baseline or with change in 25(OH)D over 12 weeks in black and white children [43].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies with vitamin D supplementation have confirmed this lack of correlation. Although daily supplementation with high-dose cholecalciferol (vitamin D3) in children and young adults with HIV infection for 12 months resulted in increased 25(OH)D concentrations, no impact was found on bone density, structure, and strength [42]. Similarly, PTH and bone turnover markers were not associated with 25(OH)D at baseline or with change in 25(OH)D over 12 weeks in black and white children [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the doses increased VitD levels, sufficiency was challenging to achieve due to the severe deficiency suffered by the HIV-1 infected population. The use of 7000 IU daily was the most effective dose (51, 56, 60, 63, 66, 78), and restored sufficiency [defined as calcidiol serum levels >30 ng/mL (4)] in 80% of treated individuals with higher levels seen following 12 months of treatment (61). Only 2 of the 215 individuals treated with this regimen had calcidiol levels >90 ng/mL and hypercalcemia (66).…”
Section: Vitamin D Supplementation In Hiv-1 Infected Individualsmentioning
confidence: 99%
“…VitD supplementation trials can be confounded by several aspects such as the season in which the study is carried out (78) or skin pigmentation since sunlight can affect vitamin levels. A study performed by Dougherty et al showed that calcidiol basal levels were lower in individuals in winter than in other seasons (63).…”
Section: Vitamin D Supplementation In Hiv-1 Infected Individualsmentioning
confidence: 99%
“…[ 62 ] and Rovner et al . [ 63 ] published a secondary analyses of muscle and bone outcomes generated by Stallings et al . [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Rovner et al . [ 63 ] was the only study to explicitly state that such height adjustments were performed whereas Arpadi et al . was the only study to report supplementary analyses of Tanner stage advancement [ 56 ].…”
Section: Discussionmentioning
confidence: 99%